1990
DOI: 10.1021/ic00342a048
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic separation and characterization of linkage isomers of the 3-(pyridin-2-yl)-1H-1,2,4-triazole complex of ruthenium(II) bis(2,2'-bipyridyl)

Abstract: Chromatographic Separation and Characterization of LinkageIsomers of the 3-(Pyridin-2-yl)-l//-l,2,4-triazole Complex of Ruthenium(II) Bis(2,2-bipyridyl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…In a study carried out by Ryan et al it was found that for ligands with a substituent on the triazole 5-position coordination occurred via both N4 and N2 in a ratio of approximately 9:1, 20 while the ratio of isomers is 1:1 when the 5-position is occupied by a hydrogen atom. 21 With HL1 only one major product was obtained in all cases. To unambiguously determine the coordination mode of the triazole ring in these compounds the X-ray structural analysis of two compounds was performed.…”
Section: X-ray Crystallographymentioning
confidence: 91%
“…In a study carried out by Ryan et al it was found that for ligands with a substituent on the triazole 5-position coordination occurred via both N4 and N2 in a ratio of approximately 9:1, 20 while the ratio of isomers is 1:1 when the 5-position is occupied by a hydrogen atom. 21 With HL1 only one major product was obtained in all cases. To unambiguously determine the coordination mode of the triazole ring in these compounds the X-ray structural analysis of two compounds was performed.…”
Section: X-ray Crystallographymentioning
confidence: 91%
“…This is in contrast with the behaviour of most common triazole complexes. [16,17] 2-D COSY spectroscopic techniques were used to assign the 1 H resonances where possible. The doublets observed at δ ϭ 9.75 and 9.42 can be attributed to the protons at positions a and c of the phenanthroline ring A respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The multicoordination capability of the triazole segment has induced formation of several isomers during reaction with the [Ru(bpy) 2 ] unit. As a consequence, effective chromatographic techniques were needed to separate these coordination isomers [22] .…”
Section: Ligand Modifi Cationsmentioning
confidence: 99%